Social-cultural, psychological, linguistic, and world knowledge; EFL students' voices on their speaking difficulties in the border area of Indonesia - Faisal Adi Putra; Ramli Ramli; Farid Helmi Setyawan (English Department FBS UNP, 2023)
This study was conducted to identify students' difficulties with English speaking. This research used a qualitative method involving six students in the fifth semester of the English department at public university in Kalimantan Utara through purposive sampling. Data collection was carried out with in-depth semi-structured interviews. This study showed that students still experienced some difficulties in speaking English. The first factor was sociocultural;1) family engagement, 2) student's environment, and 3) peer engagement. The second factor was psychological; 4) feeling afraid, and 5) shyness. The third factor was linguistic; 6) local dialect, 7) pronunciation, 8) knowledge of grammatical patterns, 9) lack of vocabulary, and 10) fillers. The fourth factor was world knowledge, 11) topical knowledge, 12. limited learning time, and 13) comprehension. This study contributed to the students' reflection on finding their appropriate learning strategies and language exposure. Besides, the teacher needed to develop professionalism to help students reduce their speaking difficulties.